2014
DOI: 10.21837/pmjournal.v12.i3.130
|View full text |Cite
|
Sign up to set email alerts
|

E-Payment at the Local Government Level: A Study of Majlis Bandaraya Shah Alam and Majlis Daerah Kampar

Abstract: Information and Communication Technology (ICT) adoption through the implementation of electronic government (e-Government) helps improves local authority's service delivery for the benefit of the community. Many of the local authorities have adopted the online payment method for the assessment rate collection. Despite the notion that e-Government increased productivity and improved efficiency, citizen's usage is still considered minimal and has been comparatively low especially in services involving transactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The result was consistent with the previous studies that also identified Effort Expectancy to have a high impact on technology adoption (Khattab et al, 2015) particularly among local authorities in Malaysia (Pitchay et al, 2016;Zahari, Ariffin, Zamin, & Noor, 2014). Effort Expectancy especially in terms of user friendliness of the service was also found to be significant in both assessing information and conducting transaction with the respective local authority's website.…”
Section: Drivers Of E-government Usesupporting
confidence: 90%
See 1 more Smart Citation
“…The result was consistent with the previous studies that also identified Effort Expectancy to have a high impact on technology adoption (Khattab et al, 2015) particularly among local authorities in Malaysia (Pitchay et al, 2016;Zahari, Ariffin, Zamin, & Noor, 2014). Effort Expectancy especially in terms of user friendliness of the service was also found to be significant in both assessing information and conducting transaction with the respective local authority's website.…”
Section: Drivers Of E-government Usesupporting
confidence: 90%
“…Effort Expectancy especially in terms of user friendliness of the service was also found to be significant in both assessing information and conducting transaction with the respective local authority's website. A study by Zahari, Ariffin, Zamin, and Noor (2014) showed that an initiative by the Shah Alam City Council (MBSA) to offer a wide range of online banking services on the their official website had increased usage as citizens had a another option to use the online payment even though the citizens had different bank accounts.…”
Section: Drivers Of E-government Usementioning
confidence: 99%
“…This necessitated the introduction of e-payments in revenue collection by LGAs to eliminate the weaknesses and anomalies exhibited by manual procedures in 2014. Zahari et al (2014) has argued that it is essential to channelize the system responsible for billing and receiving revenue to increase the collection of revenue by local authorities. In this spirit, in 2014 local authorities in Tanzania changed from manually administered system of own source revenue collection to online system of Local Government Revenue Collection Information System (LGRCIS), which is integrated with the Geographical Information System (GIS) .…”
Section: Introductionmentioning
confidence: 99%